Electrophilic RNA for Peptidyl‐RNA Synthesis and Site‐Specific Cross‐Linking with tRNA‐Binding Enzymes. (26th September 2016) - Fonvielle, Matthieu; Sakkas, Nicolas; Iannazzo, Laura; Le Fournis, Chloé; Patin, Delphine; Mengin‐Lecreulx, Dominique; El‐Sagheer, Afaf; Braud, Emmanuelle; Cardon, Sébastien; Brown, Tom; Arthur, Michel; Etheve‐Quelquejeu, Mélanie
Abstract: RNA functionalization is challenging due to the instability of RNA and the limited range of available enzymatic reactions. We developed a strategy based on solid phase synthesis and post‐functionalization to introduce an electrophilic site at the 3′ end of tRNA analogues. The squarate diester used as an electrophile enabled sequential amidation and provided asymmetric squaramides with high selectivity. The squaramate‐RNAs specifically reacted with the lysine of UDP‐MurNAc‐pentapeptide, a peptidoglycan precursor used by the aminoacyl‐transferase FemXWv for synthesis of the bacterial cell wall. The peptidyl‐RNA obtained with squaramate‐RNA and unprotected UDP‐MurNAc‐pentapeptide efficiently inhibited FemXWv . The squaramate unit also promoted specific cross‐linking of RNA to the catalytic Lys of FemXWv but not to related transferases recognizing different aminoacyl‐tRNAs. Thus, squaramate‐RNAs provide specificity for cross‐linking with defined groups in complex biomolecules due to its unique reactivity.